Zinc, a micronutrient and its effect to performance of BARI gom30 - Gismy, Salamun; Romij Uddin, Md.; Sohanur Rahman, Md.; Uddin Talukder, fakhar; Shafiul Islam Rion, Md. (International Journal of Advanced Geosciences, 2020)
To evaluate the effect of Zinc fertilizer on performance of wheat cv. BARI gom30, an experiment was carried out at Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, from November 2015 to March 2016. The experiment comprised four levels of Zinc (Zn) viz., 0, 1.5, 2 and 2.5 kg/ha. The experiment was laid out in a randomized complete block design with three replications. Application of Zinc (Zn) plant height, number of total tillers/plant, number of effective tillers/plant, spike length, number of fertile spikelets/spike numbers of sterile spikelets/spike number of grains/ spike, grain yield and straw yield were found significant. But there was no significant effect of the treatment on 1000-grain weight. The highest number of total tiller/plant (4.42), number of effective tillers/plant (3.92), number of grains/spike (47.70), 1000-grain weight (47.73 g), grain yield (5.06 t/ha), straw yield (6.21 t/ha) was obtained from 2 kg Zn/ha. The highest plant height (94.08 cm), spike length (9.92 cm), number of fertile spikelets/spike (19.59) and sterile spikelets/spike (3.22) and harvest index (46.16%) were recorded at 0 kg Zn/ha respectively. The control treatment indicated the lowest value for the yield attributing characters except the number of sterile spikelets/spike. Grain yield was found to be significantly and positively correlated with number of grains/spike and straw yield. It is recommended that application of 2 kg Zn/ha is the best for maximum yield of BARI gom30.Â Â Â